Respostas
respondido por:
2
Basta trocar x por zero:
f(0) = 3*0 + 7 = 0 + 7 = 7
f(0) = 7
cintiadessetti39:
Oi você pode me ajudar?
respondido por:
2
Olá!!
Resolução!!
Basta substituir o " x " por 0
f ( x ) = 3x + 7
f ( 0 ) = 3 • 0 + 7
f ( 0 ) = 0 + 7
f ( 0 ) = 7
Espero ter ajudado!
Resolução!!
Basta substituir o " x " por 0
f ( x ) = 3x + 7
f ( 0 ) = 3 • 0 + 7
f ( 0 ) = 0 + 7
f ( 0 ) = 7
Espero ter ajudado!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás